2002
DOI: 10.1046/j.1439-0523.2002.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a new source of resistance to powdery mildew in mungbean

Abstract: Both restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP) analyses were employed to map a new source of resistance to powdery mildew in mungbean. Disease scores of an F2 population derived from the cross between a moderately resistant breeding line VC1210A and a susceptible wild relative (Vigna radiata var. sublobata, accession TC1966) showed a continuous distribution and was treated as a quantitative trait. Although no significant quantitative trait loci (QTL) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…Several earlier studies reported monogenic inheritance of powdery mildew resistance controlled by single dominant genes and studies were conducted using mungbean varieties ML3 and ML5 (AVRDC, 1979), and breeding lines VC 1560A (AVRDC, 1981), ATF 3640 (Humphry et al, 2003) and RUM (Reddy et al, 1994a). Using restriction fragment length polymorphism (RFLP) markers, Chaitieng et al (2002) (Young et al, 1993;Sorajjapinun et al, 2005). Sorajjapinun et al (2005) reported that additive gene action was found to play a major role in controlling powdery mildew (E. polygoni) resistance in the population of crosses developed between moderately resistant KPS 2 and resistant VC 6468-11-1A (sourced from the World Vegetable Center).…”
Section: Identification Of Major Genes and Quantitative Trait Loci (Qmentioning
confidence: 99%
“…Several earlier studies reported monogenic inheritance of powdery mildew resistance controlled by single dominant genes and studies were conducted using mungbean varieties ML3 and ML5 (AVRDC, 1979), and breeding lines VC 1560A (AVRDC, 1981), ATF 3640 (Humphry et al, 2003) and RUM (Reddy et al, 1994a). Using restriction fragment length polymorphism (RFLP) markers, Chaitieng et al (2002) (Young et al, 1993;Sorajjapinun et al, 2005). Sorajjapinun et al (2005) reported that additive gene action was found to play a major role in controlling powdery mildew (E. polygoni) resistance in the population of crosses developed between moderately resistant KPS 2 and resistant VC 6468-11-1A (sourced from the World Vegetable Center).…”
Section: Identification Of Major Genes and Quantitative Trait Loci (Qmentioning
confidence: 99%
“…Several molecular markers have been used in mungbean, including amplified fragment length polymorphism (AFLP), restriction fragment length polymorphism (RFLP), random amplified polymorphic DNA (RAPD), simple sequence repeat (SSR), and inter-simple sequence repeats (ISSR) (Chaitieng et al, 2002;Afzal et al, 2004;Tangphatsornruang et al, 2009;Tantasawat et al, 2010b;Raturi et al, 2012). Afzal et al (2004) have used RAPD to evaluate the genetic diversity of 21 cultivated mungbeans from Thailand, Bangladesh, and India.…”
Section: Introductionmentioning
confidence: 99%
“…Both additive and dominant gene actions were found to be important as well as non-allelic interactions (Gawande & Patil, 2003). In lines VC1210 and ATF3640 major loci controlling resistance to this pathogen were detected using QTL analysis (Chai Tieng et al, 2002;Humphry et al, 2003). Molecular markers associated with resistance to powdery mildew of common bean have been identified (Melo et al, 2002).…”
Section: Sources Of Resistancementioning
confidence: 99%